1998
DOI: 10.1093/jaoac/81.6.1209
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 17β-Estradiol and Its Metabolites in Sewage Effluent by Solid-Phase Extraction and Gas Chromatography/ Mass Spectrometry

Abstract: The paper describes a simple and quantitative method for monitoring non-conjugated 17β-estradiol (E2) and its metabolites estrone (E1) and estriol (E3) as environmental contaminants in municipal sewage effluents. Estrogens were preconcentrated and cleaned up by solid-phase extraction using a reversed-phase c18cartridge. They were derivatized with pentafluoropropionic acid anhydride, and the products were analyzed by gas chromatography/mass spectrometry. Recoveries from spiked distilled water and sewage were be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
0
6

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 0 publications
8
66
0
6
Order By: Relevance
“…These reagents are linked in clusters in accordance with the effectiveness of derivatization: BSTFA/TMCS and pyridine (1:1, v/v) and MSTFA and pyridine were very effective, whereas the acylation of the analytes using PFPA, TFAA and HFBI was not: with these latter reagents, the corresponding acylated derivatives of EE2 were not obtained neither was the derivatization of DES completed. Our observations are in agreement with the results obtained by other scientific groups [39,40], who reported that although acylated derivatives were formed more quickly and were less sensitive to hydrolysis than the TMS derivatives of oestrogenic compounds, in many cases only the hydroxyl group on the unsaturated ring was derivatized, which resulted in just a minimal improvement in Table 2. Relative response factors (RRFs) (mean value) obtained from the silylation of oestrogenic compounds under the conditions described in Table I sensitivity.…”
Section: Influence Of the Different Derivatization Reagents On The Chsupporting
confidence: 93%
“…These reagents are linked in clusters in accordance with the effectiveness of derivatization: BSTFA/TMCS and pyridine (1:1, v/v) and MSTFA and pyridine were very effective, whereas the acylation of the analytes using PFPA, TFAA and HFBI was not: with these latter reagents, the corresponding acylated derivatives of EE2 were not obtained neither was the derivatization of DES completed. Our observations are in agreement with the results obtained by other scientific groups [39,40], who reported that although acylated derivatives were formed more quickly and were less sensitive to hydrolysis than the TMS derivatives of oestrogenic compounds, in many cases only the hydroxyl group on the unsaturated ring was derivatized, which resulted in just a minimal improvement in Table 2. Relative response factors (RRFs) (mean value) obtained from the silylation of oestrogenic compounds under the conditions described in Table I sensitivity.…”
Section: Influence Of the Different Derivatization Reagents On The Chsupporting
confidence: 93%
“…Our present study using medaka indicated that the LOEC and NOEC of E 2 were 8.66 and 2.86 ng/L, respectively, and these values well agree to those of the previous studies of EE 2 using other fish species. Natural estrogens and alkylphenols are possible candidates for estrogenic activity in the effluents from sewage treatment works [3,7,[9][10][11]. However, it is not clear to what extent these substances have risks to fish populations in real aquatic environments.…”
Section: Discussionmentioning
confidence: 99%
“…Endocrine-disrupting effects, such as a high prevalence of intersex gonads (testis-ova) or induction of the female-specific protein vitellogenin (VTG), have been reported for male fish inhabiting aquatic environments receiving effluents from sewage treatment works [3][4][5][6][7][8]. In addition, several studies have reported that the estrogenic activity of effluents from sewage treatment works may be due to the presence of natural and synthetic estrogens in the effluents [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A collaborative effort among European countries, known as Community Programme of Research on Environmental Hormones and Endocrine Disruptors (COMPREHEND), has demonstrated that estrogenic effluents occur across mainland Europe and that these include both municipal and industrial wastewaters (http:// www.ife.ac.uk/comprehend). The estrogenic activity of WWTF effluents and rivers receiving the effluents has been evaluated by fish Vtg assays [2][3][4][6][7][8][9][10], in vitro assays [11][12][13][14], and quantification of individual estrogenic compounds [12,[15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%